2003
DOI: 10.1086/374852
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ring Wearing on Hand Contamination and Comparison of Hand Hygiene Agents in a Hospital

Abstract: We determined risk factors for hand contamination and compared the efficacy of 3 randomly allocated hand hygiene agents in a group of surgical intensive care unit nurses. We cultured samples of one of the subjects' hands before and samples of the other hand after hand hygiene was performed. Ring wearing was associated with 10-fold higher median skin organism counts; contamination with Staphylococcus aureus, gram-negative bacilli, or Candida species; and a stepwise increased risk of contamination with any trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 39 publications
6
103
1
7
Order By: Relevance
“…Contamination rate was not significantly different between those who used hand rub routinely during posting and those who did not. An earlier study has reported that compared to uncleansed hands, hands cleansed with alcohol-based hand rub were significantly less likely to be contaminated with methicillin-resistant CoNS [20]. The contamination rates of those who agreed to have received formal training in hand hygiene were comparable to those who did not.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Contamination rate was not significantly different between those who used hand rub routinely during posting and those who did not. An earlier study has reported that compared to uncleansed hands, hands cleansed with alcohol-based hand rub were significantly less likely to be contaminated with methicillin-resistant CoNS [20]. The contamination rates of those who agreed to have received formal training in hand hygiene were comparable to those who did not.…”
Section: Discussionmentioning
confidence: 89%
“…In a study conducted among dentists, bacteria and fungi were significantly more frequent in dentist's hand with rings than those without rings (63% and 37% respectively) and among the isolated, potentially pathogenic microorganisms were S. aureus, E. coli, and Candida albicans [26]. Another study among nurses, the presence of rings on hands resulted in an increased frequency of hand carriage of S. aureus as well as Gram-negative bacilli [20].…”
Section: Senthil Et Almentioning
confidence: 99%
“…Moreover, laboratory technicians are exposed to laboratory associated infections through various routes. Contaminants from workers' hands, mobile phones, jewelleries and other personal objects that are brought into the laboratory are mechanical vectors of laboratory associated infections [5][6][7]. To alleviate these risk factors, working at such laboratories require biosafety measures designed to protect the staff, the population and the environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…6 Increasingly, NICUs have stethoscopes available at each bedside for caregivers to share; failing that, stethoscope cleaning is yet another step that has to be routinely enforced. Healthcare workers bring a host of other potentially contaminated objects to the bedside -from rings 7 and neckties 8 to our venerable white lab coats, 9 which, if not laundered every 2 days, may carry more germs than they block. Most NICUs no longer have mandatory gown policies, as they have not been proven to be effective in reducing NI in the NICU, 10 with the suspicion that gowning may lead to less vigilant hand hygiene.…”
mentioning
confidence: 99%